Genome Sequence of the Oligotrophic Marine Gammaproteobacterium HTCC2143, Isolated from the Oregon Coast - Oh, Hyun-Myung (American Society for Microbiology (ASM), 2010)
Strain HTCC2143 was isolated from Oregon Coast surface waters using dilution-to-extinction culturing. Here we present the genome of strain HTCC2143 from the BD1-7 clade of the oligotrophic marine Gammaproteobacteria group. The genome of HTCC2143 contains genes for carotenoid biosynthesis and proteorhodopsin and for proteins that have potential biotechnological significance: epoxide hydrolases, Baeyer-Villiger monooxygenases, and polyketide synthases.